Venom-Induced Blood Disturbances by Palearctic Viperid Snakes, and Their Relative Neutralization by Antivenoms and Enzyme-Inhibitors - Chowdhury, Abhinandan; Zdenek, Christina N.; Lewin, Matthew R.; Carter, Rebecca; Jagar, Tomaž; Ostanek, Erika; Harjen, Hannah; Aldridge, Matt; Soria, Raul; Haw, Grace; Fry, Bryan G. (Frontiers in Immunology, 2021)
Palearctic vipers are medically significant snakes in the genera Daboia, Macrovipera, Montivipera, and Vipera which occur throughout Europe, Central Asia, Near and Middle East. While the ancestral condition is that of a small-bodied, lowland species, extensive diversification has occurred in body size, and niche specialization. Using 27 venom samples and a panel of in vitro coagulation assays, we evaluated the relative coagulotoxic potency of Palearctic viper venoms and compared their neutralization by three antivenoms (Insoserp Europe, VIPERFAV and ViperaTab) and two metalloprotease inhibitors (prinomastat and DMPS). We show that variation in morphology parallels variation in the Factor X activating procoagulant toxicity, with the three convergent evolutions of larger body sizes (Daboia genus, Macrovipera genus, and Vipera ammodytes uniquely within the Vipera genus) were each accompanied by a significant increase in procoagulant potency. In contrast, the two convergent evolutions of high altitude specialization (the Montivipera genus and Vipera latastei latastei uniquely within the Vipera genus) were each accompanied by a shift away from procoagulant action, with the Montivipera species being particularly potently anticoagulant. Inoserp Europe and VIPERFAV antivenoms were both effective against a broad range of Vipera species, with Inoserp able to neutralize additional species relative to ViperFav, reflective of its more complex antivenom immunization mixture. In contrast, ViperTab was extremely potent in neutralizing V. berus but, reflective of this being a monovalent antivenom, it was not effective against other Vipera species. The enzyme inhibitor Prinomastat efficiently neutralized the metalloprotease-driven Factor X activation of the procoagulant venoms. In contrast, DMPS (2, 3-dimercapto-1-propanesulfonic acid), which has been suggested as another potential treatment option in the absence of antivenom, DMPS failed against all venoms tested. Overall, our results highlight the evolutionary variations within Palearctic vipers and help to inform clinical management of viper envenomation.